1999
DOI: 10.1080/07448489909595677
|View full text |Cite
|
Sign up to set email alerts
|

The Hassles Assessment Scale for Students in College: Measuring the Frequency and Unpleasantness of and Dwelling on Stressful Events

Abstract: Development of the Hassles Assessment Scale for Students in College, a new scale to measure students' stress, is described. In the scale, students rate each of 54 hassles for its frequency and unpleasantness in the past month and indicate the degree to which they dwelt or ruminated on it. Very high levels of internal consistency for the frequency, unpleasantness, and dwelling measures were found. Correlational analyses demonstrated the scale's criterion validity (scores were negatively correlated with the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 25 publications
1
30
1
2
Order By: Relevance
“…Examples of such inventories include; the Life Experience Survey (Saroson et al 1978), the Hassles Scale (Kanner et al 1981), the Social Support Inventory (Pennebaker 1982), the Hassles Assessment Scale for Students in College (Sarafino et al 1999), Student Life Stress Inventory (Gadzella 1991), the College Chronic Life Stress Survey (Towbes et al 1996), the Student Stress Scale (Insel et al 1985), the Perceived Stress Scale (Cohen et al 1989) and the Academic Stress Scale (Abouserie 1994).…”
Section: Previous Studies Into Students and Stressmentioning
confidence: 98%
“…Examples of such inventories include; the Life Experience Survey (Saroson et al 1978), the Hassles Scale (Kanner et al 1981), the Social Support Inventory (Pennebaker 1982), the Hassles Assessment Scale for Students in College (Sarafino et al 1999), Student Life Stress Inventory (Gadzella 1991), the College Chronic Life Stress Survey (Towbes et al 1996), the Student Stress Scale (Insel et al 1985), the Perceived Stress Scale (Cohen et al 1989) and the Academic Stress Scale (Abouserie 1994).…”
Section: Previous Studies Into Students and Stressmentioning
confidence: 98%
“…To date, hassles and uplifts have been examined mainly in the area of work satisfaction (Hart et al, 1994(Hart et al, , 1995Lazarus, 1995) and the quality of college student life (Blankstein et al, 1991;Sarafino and Ewing, 1999). Specifically, Van Katwyk et al (2000) research revealed that work stressors were significant predictors of job satisfaction and affective well-being.…”
Section: Introductionmentioning
confidence: 95%
“…Sarafino and Ewing (1999) subsequently broadened the definition of hassles. Their research found that common annoyances or irritants ranging from minor annoyances to fairly major pressures, problems, or difficulties could also be considered hassles.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Job stress has been implicated in the onset and maintenance of so many acute and chronic diseases, scientific priorities have shifted to focus on primary and secondary prevention strategies by way of stress reduction and stress management techniques in order to reduce the burden of disease on the population (Ebrahim & Davey Smith, 1998;Schneiderman, Antoni, Saab, & Ironson, 2001;Kromhout, Menotti).Though stress is a universal construct that affects all humans, studies shows that different populations are known to have different stressors (Sarafino & Ewing, 1999;Morrison & O'Connor, 2005) Several studies have highlighted the deleterious consequences of high workloads or work overload. According to Beehr, (1995) work overloads and time constraints were significant contributors to work stress among community nurses.…”
Section: Introductionmentioning
confidence: 99%